Penatalaksanaan Asuhan Kebidanan Pada Ibu Nifas Dengan Bendungan ASI - Pipit Indra L; Novia Putri Ramadhani (MEJORA Medical Journal Awatara, 2025)
Comprehensive midwifery care is a continuous service that includes antenatal, intrapartum, postpartum, newborn, and family planning care. This report aims to describe the midwifery care provided to Mrs. A (32 years old, G2P1A0) at 37 weeks and 2 days of gestation, conducted at Sindanglaut Public Health Center, Cirebon Regency, from February to May 2025. The method used was a case study with a continuity of care approach. Data were collected through interviews, observations, physical examinations, and SOAP documentation. During the antenatal period, both maternal and fetal conditions remained within normal limits. Spontaneous labor occurred on April 9, 2025, at 02:40 AM, resulting in the birth of a healthy male infant (weighing 2880 grams, measuring 49 cm), with strong crying and successful Early Initiation of Breastfeeding (EIBF). On postpartum day 21, the mother experienced breast engorgement in the left breast. This was managed through breastfeeding education, proper latching techniques, warm and cold compresses, and lactation massage, which effectively resolved the complaint. By postpartum day 30, both mother and baby were in good condition, and the mother opted for a 3-month injectable contraceptive method. The care provided adhered to midwifery standards and produced optimal outcomes. This report is expected to serve as a reference for healthcare providers in delivering comprehensive and continuous midwifery care